Volunteers Experiences for the Future of Disaster Education: Empowering Communities, Addressing Challenges, and Charting a Resilient Future - Seyfullah Gül; Eyüp Artvinli (Acta Paedagogica Vilnensia, 2024)
Volunteers are tremendous resources in space and time scale with their global footprints, qualifications, and scopes. However, volunteers are often ignored, especially in dealing with disasters. This study has been carried out to identify the basic problems that will shape the future education of volunteers working in disasters, based on real-life case studies. In this study, a qualitative case study method was used to focus on the activities completed by volunteers in the event of a disaster, and therefore reveal the problems which are experienced by volunteers. The data has been collected through participant observation and semi-structured interviews. Descriptive analysis was used to analyze the data. According to findings six themes of (1) participation, (2) quality, (3) attitude, (4) impact, (5) problems and (6) suggestions are determined as being related to the activities of volunteers who respond to and deal with disasters. The findings also indicate that although volunteers can easily join volunteer organizations in Türkiye, there are problems arising from disaster victims, volunteer organizations and volunteers. Consequently, whilst volunteers in Türkiye are important actors in dealing with disasters, it is thought that volunteers can be utilized much more and at a qualified level in the fight against disasters.